1981
DOI: 10.1530/jrf.0.0620141
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and follicular relationships in ewes of high and low ovulation rates

Abstract: Total follicular populations and peripheral plasma concentrations of LH, FSH, prolactin, oestradiol-17 beta and progesterone during the preceding cycle were studied in two breeds of sheep (Romanov and Ile-de-France) which differed widely in their ovulation rates (3.2 and 1.5 respectively). No LH parameters could be correlated with the follicular details measured. The second peak of FSH occurring 20-30 h after the preovulatory surge of LH was significantly larger in the Romanov ewes and the area under this peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 18 publications
11
45
1
Order By: Relevance
“…(The amount of LH discharged was not related to ovulation rate.) The physiological significance of this phenomenon was questioned by Cahill et al (1981) in their study of the Romanov breed, since the number of ovulatory follicles is already decided by this time. In any event the Booroola did not conform to the pattern of other prolific sheep in this regard with both Booroola and controls having an LH discharge about 4· 5 h after the onset of oestrus (Table 8).…”
Section: Role Of Lh and Lh Pulse Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…(The amount of LH discharged was not related to ovulation rate.) The physiological significance of this phenomenon was questioned by Cahill et al (1981) in their study of the Romanov breed, since the number of ovulatory follicles is already decided by this time. In any event the Booroola did not conform to the pattern of other prolific sheep in this regard with both Booroola and controls having an LH discharge about 4· 5 h after the onset of oestrus (Table 8).…”
Section: Role Of Lh and Lh Pulse Frequencymentioning
confidence: 99%
“…When FSH concentrations were compared over broad time periods (PG to onset of oestrus; during oestrus; from end of oestrus for 24 h), there were no significant differences between the genotypes. This type of study was repeated in more detail by Cahill et al (1981) in the normal oestrous cycle, and the FSH profiles were aligned with respect to the pre-ovulatory LH discharge. In this case Romanov ewes had a significantly (P<O· 05) greater day 2 FSH peak than another breed.…”
Section: Role Of Fsh In Regulation Of Ovulation Ratementioning
confidence: 99%
“…Similar breed differences in the concentration of E 2 before the surge have been observed during the breeding season and have often been linked with the prolificity of the breed (Land et al 1976, Cahill et al 1981. In one study using both intact and ovariectomised ewes, Ben Saïd et al (2007) showed that Romanov ewes, a breed that has multiple ovulations, require higher concentrations of E 2 and for a longer duration for the induction of a LH surge than IF ewes.…”
Section: Discussionmentioning
confidence: 75%
“…The LH surge occurs only after a period of prolonged exposure to the above threshold concentrations of E 2 (Corker et al 1969, Karsch et al 1973, 1979, Smith et al 1975, Hauger et al 1977. In sheep, the characteristics of the relationship between the preovulatory rise in systemic concentrations of E 2 and the onset of the LH surge, and presumably of GNRH, varies among breeds (Land et al 1976, Cahill et al 1981, Ben Saïd et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The use of gonadotrophic pituitary extracts for ovarian hyperstimulation enhances embryo production (Martemucci et al, 1988;Jabbour and Evans, 1991). Taking into account the physiological hormonal pattern from luteal regression and preovulatory peak in LH (Cahill et al, 1981), several studies have demonstrated that the daily FSH/LH ratio during treatment appears to be important in the superovulatory response in small ruminants for in vivo embryo production (Chupin et al, 1987;Baril et al, 1989;Martemucci et al, 1996;D'Alessandro et al, 1997).…”
Section: Introductionmentioning
confidence: 99%